2018
DOI: 10.9734/air/2018/39876
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Contamination of Table Eggs Sold in Khartoum State, Sudan

Abstract: Aim:The current study was conducted to assess fungal contamination of table eggs sold in Khartoum State, Sudan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
(18 reference statements)
5
4
2
Order By: Relevance
“…The literature showed that the vast majority of OSCC cases worldwide occur in the fifth to the eighth decade of life [13,14]. Similar to our result, the other previous Sudanese studies reported a median age of 53-60 years at the initial presentation [3,6,15]. Although the last two decades showed a noticeable involvement in the young age groups, as reported by Liu et al [16], worldwide incidence rates of oral cancer differ dramatically between both genders due to different environmental and social factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The literature showed that the vast majority of OSCC cases worldwide occur in the fifth to the eighth decade of life [13,14]. Similar to our result, the other previous Sudanese studies reported a median age of 53-60 years at the initial presentation [3,6,15]. Although the last two decades showed a noticeable involvement in the young age groups, as reported by Liu et al [16], worldwide incidence rates of oral cancer differ dramatically between both genders due to different environmental and social factors.…”
Section: Discussionsupporting
confidence: 90%
“…The sort of carcinogenic material, duration of tissue contact and dose, frequency, and combination of the different carcinogens; all are involved with different degrees in the process of cancer development [5]. Top on the carcinogenic materials is tobacco in its different forms of usage [6]. Toombak is a moist form of snuff, well known as a risk factor of oral squamous cell carcinoma (OSCC) in Sudan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also analysis of variance (ANOVA) was used for comparison between the different age groups using Statistical Package for Social Sciences (SPSS) computer package version 20. At 95% confidence level of p. value <0.05 was considered statistically significant Results: 15.3%, their mean age was 46.7years (ranged between 28 to 75 years), Female to male ratio was 5.5:1 (table 2) Our findings are similar to a study in our local population by (Suleiman, 1977) and from , Iraq. By (Hadi et al, 2012) which revealed that, the ratio of female to male were 5.3:1 and 5:1 respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Regecová et al [26] reported the occurrence of microscopic filamentous fungi of Penicillium spp., Aspergillus spp., Cladosporium spp., and Alternaria alternate group in chicken eggs. Similar results were obtained by Rajmani et al [34]. In the study of Neamatallah et al [35], 38% of the eggs examined were contaminated with spores of potentially toxinogenic Penicillium, Aspergillus, and Fusarium species.…”
Section: Discussionsupporting
confidence: 81%